Design of hetero-nanojunction of RGO/\(\alpha\)-Fe\(_2\)O\(_3\) nanofibers for ethanol gas sensor - Phan, Hong Phuoc; Le, Viet Thong; Nguyen, Van Hoang; Nguyen, Duc Hoa; Nguyen, Van Duy; Nguyen, Ngoc Viet; Nguyen, Van Hieu (Communications in Physics, 2023)
Enhanced gas sensing properties of hematite \(α\)-Fe2O3 by loaded reduced graphene oxides (RGO) have attracted considerable attention. In this study, RGO-loaded \(α\)-Fe2O3 nanofibers were fabricated via the facile electrospinning method and subsequent calcination process. The scanning electron microscopy (SEM) images showed that RGO-loaded \(α\)-Fe2O3 nanofibers with diameters of 50-100 nm have typical morphologies of spider nets. The X-ray diffraction (XRD) patterns revealed the rhombohedral structure of the RGO-loaded α-Fe2O3 nanofibers. The energy dispersive X-ray spectroscopy (EDS) results exhibited the presence of Fe, O, and C elements in the synthesized nanofibers. The gas sensing results also confirmed that the sensors based on RGO-loaded \(α\)-Fe2O3 nanofibers could be applied for detecting ethanol gas.